Letter (copy) : International Brigade Dependants and Wounded Aid Committee - Tewson, Vincent
034-0105-001 Secretary's. HVT/FC/EK/490. P. 22nd December, 1938. Mr. W. Stott, Railway Clerks' Association, 25, Euston Road, London, N.W.1. Dear Mr. Stott, International Brigade Dependants and Wounded Aid Committee With further reference to our correspondence on the above subject, I may say that the General Council at their meeting yesterday decided that the previous decision taken on the question of assistance on behalf of the dependents and wounded members of the International Brigade, namely, "that in the circumstances no action could be taken on the lines proposed", should be adhered to. Wishing you the compliments of the Season. Yours sincerely, Assistant Secretary. 292/946/34/105